IL-17A promotes the progression of Alzheimer’s disease in APP/PS1 mice - Min Cao; Jing Liu; Xiaomin Zhang; Yaqi Wang; Yuli Hou; Qiao Song; Yuting Cui; Yue Zhao; Peichang Wang (Immunity & Ageing, 2023)
Abstract Background Alzheimer’s disease (AD), which is the most common cause of dementia in elderly individuals, is a progressive neurodegenerative disorder. Neuroinflammation, which is an immune response that is activated by glial cells in the central nervous system, plays an important role in neurodegenerative diseases. Many studies have shown that interleukin-17A (IL-17A) plays an important role in AD, but research on the pathological effects of IL-17A on AD is limited. Methods We report the effect of IL-17A on AD progression in APPswe/PS1dE9 (APP/PS1) mice, which are the most widely used AD model mice. The BV2 cell line, which is a microglial cell line derived from C57/BL6 mice, was used to establish a cell model to verify the role of IL-17A in neuroinflammation at the cellular level. The HT22 hippocampal neuronal cell line was used to investigate the relationship between IL-17A and Aβ deposition. Results In this research, we found that IL-17A promotes the progression of AD in the APP/PS1 mouse model. The role of IL-17A in neuroinflammation is related to tumour necrosis factor (TNF)-α. Circulating IL-17A stimulates the secretion of TNF-α by microglia through the Toll-like receptor 4 (TLR4)/nuclear factor (NF)-κB signalling pathway, thus exacerbating neuroinflammation. In addition, intraperitoneal injection of IL-17A antibody (IL17Ab) significantly improved the cognitive function of APP/PS1 mice. Conclusions IL-17A increased TNF-α levels in the brain and exacerbated neuroinflammation through the TLR4/NF-κB signalling pathway and microglial activation in APP/PS1 mice. Moreover, IL-17A promoted the progression of AD by enhancing neuroinflammation, inhibiting microglial phagocytosis, and promoting the deposition of β-amyloid 42 in AD model mice.